SAT0364 DATA TO BE COLLECTED FOR AN OPTIMAL MANAGEMENT OF AXIAL SPONDYLOARTHRITIS IN DAILY PRACTICE: PROPOSAL FROM AN EVIDENCE BASED AND CONSENSUAL APPROACHES. (2nd June 2020) - Baillet, A.; Romand, X.; Pfimlin, A.; Dalecky, M.; Dougados, M.
Abstract : Background: Standardization of clinical practice has been proven to be effective in management of chronic diseases. This is particularly true at the time where the concept of treat to target is becoming more and more important in the field of axial spondyloarthritis (ax-SpA). Objectives: To propose a list of variables to be collected at the time of the diagnosis and over the follow-up of patients with axial spondyloarthritis (ax-SpA) for an optimal management in daily practice. Methods: The process comprised (1) the evaluation of the interest of 51 variables proposed for the assessment of axSpA via a systematic literature research, (2) a consensus process involving 78 hospital-based or office-based rheumatologists, considering the collection of the variable in a 4 grade scale from "potentially useful" to "mandatory", (3) a consensus on optimal timeline for periodic assessment of the selected variables on a 5 grade scale from "at each visit" to "never to be re-collected". Results: The systematic literature research retrieved a total of 14, 133 abstracts, of which 213 were included in the final qualitative synthesis. Concerning the data to be collected at the time of the diagnosis and during follow-up, we proposed to differentiate the results based on a) the way of collection of the variables (e.g. questionnaires by the patient, interview by the physician, physical examination, investigations) b) the usefulness these variables in daily practice based on the opinion of the rheumatologists " c) the optimal timeline between 2 evaluations of the variable based on the opinion of the rheumatologists. In the initial systematic review, symptoms of heart failure history of inflammatory bowel disease, psoriasis or uveitis, patient global visual analogic scale, spine radiographs, modified Schöber test, coxo-femoral rotations, swollen joint count, urine strip test, BASDAI and ASDAS global scores were considered very useful and nocturnal back pain/morning stiffness, sacro-iliac joints radiographs and CRP were considered mandatory (Figure 1 ). Timeline between 2 evaluations of variables to collect in the periodic review are summarized in Figure 2 . Conclusion: Using an evidence-based and an expert consensus approaches, this initiative defined a core set of variables to be collected and reported at the time of the diagnosis and during follow-up of patients with ax-SpA in daily practice. Acknowledgments: this study has been conducted in two parts: the first one (evidence-based) was conducted thanks to a support from Abbvie France. AbbVie did not review the content or have influence on this manuscript. The second part of this initiative (consensus) has been conducted thanks to a support from the scientific non-profit organization: Association de Recherche Clinique en Rhumatologie Disclosure of Interests: Athan Baillet Consultant of: Athan BAILLET has received honorarium fees from Abbvie for his participation as the coordinator of the systematic literature review, Xavier Romand Consultant of: Xavier ROMAND has received honorarium fees from Abbvie, Arnaud Pfimlin Consultant of: Arnaud PFIMLIN has received honorarium fees from Abbvie, Mickael Dalecky Consultant of: Mickael DALECKY has received honorarium fees from Abbvie, Maxime Dougados Grant/research support from: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Consultant of: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Speakers bureau: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma